Orbital corticosteroid injections for the treatment of active thyroid eye disease - Eid, Kevin T.; Kally, Peter M.; Kahana, Alon (Frontiers in Ophthalmology, 2024)
Purpose To study the efficacy of orbital injections of triamcinolone acetonide mixed 1:1 with dexamethasone in the treatment of active thyroid eye disease. Methods Patients that received orbital injection(s) of triamcinolone acetonide mixed 1:1 with dexamethasone for thyroid eye disease were included in this retrospective study. Demographic and clinical data were collected from the pre-treatment and 1 month follow up evaluations. Clinical data included subjective pain and diplopia scores, best-corrected visual acuity, Intraocular pressure, extraocular motility, clinical activity score, Hertel exophthalmometry, and upper eyelid margin to reflex distance. Results Fifteen patients, 33 orbital injections, were included in the study. The average patient age was 59.2 years (SD ± 13.0) and 89% female. Subjectively, 67% of patients reported improvement of orbital pain and pressure versus 28% stable and 5% worse (p <0.001). Post-procedure clinical activity score decreased from 3.84 to 3.00 (p = 0.0004). There were no significant differences in upper eyelid margin to reflex distance (4.1 ± 1.4 mm vs. 4.3 ± 2.6 mm, p = 0.45), Hertel exophthalmometry (21.7 ± 9.4 mm vs. 21.8 ± 7.6 mm, p = 0.56), or extraocular motility (21% improved vs. 72% stable and 7% worsening, p = 0.50). No steroid-responsive increases in intraocular pressure or injection-related complications were reported. Conclusion Orbital steroid injections can successfully reduce symptoms of TED and may be a reliable tool in the treatment of TED as a relatively safe, fast-acting, efficacious treatment option, particularly as a bridge to other therapies.